Dr Jimmy Smith, Director General at International Livestock Research Institute (ILRI) - Smith, Jimmy W. (Wandieville Media, 2018)
Wandie Kazeem interviewing Dr Jimmy Smith, Director General at the Internatonal Livestock Research Institute at IITA 50th Anniversary, Ibadan Nigeria. The Institute focuses its research on building sustainable livestock pathways out of poverty in low-income countries. ILRI works with partners worldwide to help poor people keep their farm animal alive and productive, increase and sustain their livestock and farm productivity. In this interview Dr Jimmy Smith discussed the Farmers/Herdsmen crises and congratulates IITA on being 50.